Comparison of Phenolic Content in Cabernet Sauvignon and Saperavi Wines - Sergazy, Shynggys; Gulyayev, Alexandr; Dudikova, Galina; Chulenbayeva, Laura; Nurgaziyev, Madiyar; Krivyh, Elena; Nurgozhoina, Ayaulym; Ziyat, Arailym; Tritek, V.; Kozhakhmetov, Samat S.; Kushugulova, Almagul R. (Faculty of Biotechnology and Food Sciences, Slovak University of Agriculture in Nitra, 2019)
Several studies reveal that the phenolic compounds present in the wine and their concentrations determine physiological activities of the red wine. In this study, the main polyphenol components, including hydroxycinnamic acids, flavones, flavan-3-ols and stilbenoids, were investigated via HLPC-UV in the “Cabernet Sauvignon” and “Saperavi” wines selected from different regions and different years. In assistance of a meta-analysis, we found that there are no fundamental differences in phenolic compounds between the wines Cabernet Sauvignon and Saperavi. However, the amounts of several important phenolic materials such as catechin, caffeic acid, p-coumaric acid, chlorogenic acid and myricetin significantly higher in Saperavi wine as compared to Cabernet Sauvignon. Moreover, on the basis of the correlation analysis, we assume that flavones synthesis and regulation of stilbenoids coordinated to a greater extent in “Saperavi” than in “Cabernet Sauvignon”.